Uncertainty quantification and seismic fragility of base-isolated liquid storage tanks using response surface models. (January 2016) - Saha, Sandip Kumar; Matsagar, Vasant; Chakraborty, Subrata
Abstract: Seismic response of base-isolated liquid storage tank is represented using response surface model (RSM) to consider the uncertainty in the isolator parameters. The effectiveness of RSM to represent the probability distributions of the peak seismic response quantities of the base-isolated liquid storage tank is studied in the framework of Monte Carlo (MC) simulation. Broad and slender configurations of the tanks isolated by lead–rubber bearing (New Zealand – NZ system) characterized with non-linear force-deformation behavior is considered in the present study. The influence of the uncertain isolator parameters on the seismic response of the base-isolated liquid storage tanks is investigated. Subsequently, seismic fragility of the base-isolated liquid storage tanks is evaluated using the RSM based MC simulation. The RSM estimates the non-linear seismic response of the base-isolated liquid storage tanks with sufficient accuracy. It is observed that the uncertainties in the isolator parameters significantly influence the peak response quantities of the base-isolated liquid storage tanks. The effectiveness of the base isolation technique, in terms of the reduced probability of failure, is observed by comparing the fragility curves for the fixed-base and base-isolated liquid storage tanks. It is also observed that increase in the isolation time period decreases the probability of failure for the base-isolated liquid storage tanks. It is concluded that the peak ground acceleration (PGA) of the earthquake ground motion can be included in the RSM to reduce the computational efforts for seismic fragility analysis. Highlights: Seismic fragility of base-isolated liquid storage tanks is investigated. A computationally efficient approach for seismic fragility analysis is presented. Uncertainties in isolator parameters are considered using response surface model. Effect of isolation time period on seismic fragility is investigated.